THE SIGNIFICANCE OF SUPPLIER RELATIONSHIP MANAGEMENT IN INDUSTRY COMPETITIVENESS: A CASE OF BAKERIES IN HARARE, ZIMBABWE - Chari, Felix (IJRDO - Journal of Business Management, 2016)
This study investigates the significance of supplier relationship management on the competitiveness of the manufacturing firms in Zimbabwe. The main research problem was based on the fact that the traditional and transactional buyer supplier relationships, which focus on the price alone, no longer delivered competitive advantage to manufacturing firms in the bakery industry. The research was descriptive survey in form of a case study and qualitative methodology was mainly accommodated. The total target population was thirty and the whole target population was used, no samples were conducted. Questionnaires were distributed in person to sample staff and its input suppliers as a way of collecting data. The research found out that supplier relationship management is significant to improve organisational competitiveness typically in improving supplier responsiveness and reducing of procurement costs in bread manufacturing companies. Moreover, maintaining trust and credibility and cooperating with suppliers were found to be the main strategies for supplier relationship management. However, poor quality information technology and lack of senior management support hindered successful supplier relationship formation. Based on the findings, the main recommendations are that companies must move towards supplier relationship management and recognize its importance as a strategic tool for company competitiveness.